2021
DOI: 10.1590/1807-1929/agriambi.v25n2p109-115
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of humic substances in an Oxisol fertilized with pig slurry for 15 years

Abstract: The growth of swine production in Brazil has increased the amount of production and use of pig slurry (PS) as soil fertilizer. This product provides nutrients to plants, and a continuous application of this residue usually increases total soil organic carbon (SOC) content. The objective of this study was to determine the SOC content and its distribution into humic substance fractions (humic acids, fulvic acids, and humin) in an Oxisol annually fertilized with PS for 15 years. The experiment was implemented in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Tanzânia for the use of increasing S rates. In addition, the use of S fertilizers can increase the shoot and root biomass production of Tifton-85 and Brachiaria decumbens Stapf., and the uptake of S is dependent on the grass species; Tifton-85 is more responsive to S fertilizers and presents a higher S absorption; however, the application of high rates of S may exceed the plant requirement and increase soil S contents [42,81,82].…”
Section: Soil Bulk Density and Carbon Nitrogen And Sulfur Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tanzânia for the use of increasing S rates. In addition, the use of S fertilizers can increase the shoot and root biomass production of Tifton-85 and Brachiaria decumbens Stapf., and the uptake of S is dependent on the grass species; Tifton-85 is more responsive to S fertilizers and presents a higher S absorption; however, the application of high rates of S may exceed the plant requirement and increase soil S contents [42,81,82].…”
Section: Soil Bulk Density and Carbon Nitrogen And Sulfur Contentsmentioning
confidence: 99%
“…Maize and oat crop rotations under the long-term application of PS were evaluated by Sacomori et al [42], who found an increase in soil organic carbon in the soil 5-10 cm layer for PS rates of up to 100 m 3 ha −1 , and by Mafra et al [43], who found increasing soil organic carbon contents and stocks as the PS rates and soil layers were increased. Santos et al [44] evaluated nutrient contents of an Oxisol fertilized with PS in the Cerrado biome, Brazil, and found no differences in N stocks; they attributed it to the PS rates applied, high organic matter contents, and leaching, since the N stocks were higher in the deeper layers; in addition, they found increases in sulfur contents in the plant biomass and attributed it to the high soil N, organic matter, and clay contents, which facilitate sulphate absorption; it reflected on the biomass production and nutrient content of the Tifton-85 pastures.…”
Section: Introductionmentioning
confidence: 99%
“…Aliphatic structures prevail in the new organic matter incorporated to the soil, which would be degraded if conditions were favourable because of their faster mineralization rate, as reported in other experiments (Almendros et al, 2018; Madrid et al, 2004). Nevertheless, the sustained annual application of slurry should be taken into account since the benefits in soil physical quality (Bosch‐Serra et al, 2017; Mateo‐Marín et al, 2021; Yagüe, Bosch‐Serra, Antúnez, & Boixadera, 2012) can be related not only to the SOM increase but also to changes in its composition (Álvarez et al, 2013; Sacomori et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, long‐term compositional studies on HTS are still scarce (Ferrari et al, 2011; Francioso et al, 2000; Zhang et al, 2017), even though they are needed to contribute with field data in the framework of ‘A Soil Deal for Europe’, towards healthy soils (European Commission, 2020). In particular, a series of investigations in recent years have focused their interest on characterizing the changes in the molecular composition of humic substances accumulated in the soil after the application of slurry (Benedet et al, 2020; Furtado e Silva, Do Amaral Sobrinho, et al, 2022; Furtado e Silva, García, et al, 2022; Sacomori et al, 2021; Yagüe & Lobo, 2020).…”
Section: Introductionmentioning
confidence: 99%